Solving a bus driver scheduling problem: A genetic algorithm approach - Ramli, Razamin; Ibrahim, Haslinda; Lim, Tze Shung (Universiti Utara Malaysia Press, 2013)
Many transport companies face problems in regulating their transport services due to various challenges and issues. These problems affect the quality of the services provided especially in a university campus environment, where students heavily depend on the university transport services for their daily commuting.What are the problems faced by the management of the campus transport company? What are the issues raised by the drivers operating the on-campus buses?Hence, in assisting the management of the transport company the authors have identified the inefficiency of their bus driver scheduling system as one of the main problems, which needed to be tackled.For that reason, the authors developed an efficient bus driver scheduling model based on the Genetic Algorithm (GA) approach.The GA model is able to provide some resolutions and insight in relation to these inquiries: What are the constraints being considered in this bus driver scheduling problem?·How were the drivers’ break times being distributed in this GA approach?·How was the time taken to generate an efficient schedule?